(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The study was carried out on 60 persons, patients with non small cell lung cancer was conducted in the Central Euphrates Center for Tumors and the Histopathology Lab in Al- Sadr Medical City from 12-12-2015 to 12 - 7-2016. The results of the histological study showed that the adenocarcinoma contains large numbers of columnar cells that multiply along the septae, which extend between the alveolar sac. Tumor cells are large, polymorphism with clear and prominent nuclei. Cells form structure papillae. Sometimes, these structures contain necrosis foci, whereas squamous cell carcinoma (SCC) is a large bulk of multilayered, The cyst of tumor may contain or necrosis and fibrosis , while large cell carcinoma cells (LCC) appear large rounded cells with a large nucleus and foamy cytoplasm